Kinship as a Social Capital in Rural Development: An Anthropological Perspective - Aryal, Rudra (Dhaulagiri Journal of Sociology and Anthropology, 2018)
This paper is the study of institutional and organizational aspects of the management system of a community based micro hydropower. It mainly focuses on the role of kinship as well as social capital for the sustainability of micro hydropower management. However, social capital has been analyzed as one of the fundamental sources of kinship organization. This study also emphasizes on the social transformation that is only possible with an effective social mobilization and reliable institutional sources. An organized form of management system for micro hydro is functioning continuously due to the consistent engagement of community, proper mobilization of groups/institutions and institutional guidance, where social and cultural substances are primarily embedded. Ethnographic fieldwork was the principal data collection method. Both direct and indirect participant observations were used to garner the substantial amount of data. In-depth nature of semistructured interviews on various social, structural and cultural aspects was used to conduct the key interviews. To make the representative units inclusive, twenty people were purposively selected for key informant interviews including male, female and from the various occupation status. The related structural issues as well as regarding the entire management system of micro hydropower were probed through the informal interviews and group discussions to enhance the ethnographic data.